IN-SITU EXPERIMENT OF CROSS-FLOW SAVONIUS HYDROKINETIC TURBINE WITH A DEFLECTOR - Satrio, Dendy; Wiyanto, Andreas Anthoni; M, Mukhtasor (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2022)
The crossflow type Savonius turbine is capable to rotate at low current velocity conditions. The drawback of this turbine lies on its efficiency. This study aims to test its performance before implementation in the field. The research method used is an in-situ experimental study in Umbulan, Pasuruan. Turbine model T1 AR 1.145 without deflector is used, when TSR reaches a value of 0.824, it gets a CQ value of 0.327 and a CP value of 0.269. In the same model with deflector, when TSR reaches a value of 1.1, the CQ value is 0.251, and the CP value is 0.276. It can be concluded that this turbine is suitable for area with low current velocity.